1395 The Influence of Shortened Antimicrobial Courses in Surgical Management of Mid 1/3rd Facial Fractures. (12th October 2021) - Lawrence, M; Karia, R; George, K
Abstract: Aim: Antimicrobial resistance (AMR) is an increasing issue posing a grave threat to global public health. A prospective pilot study within our OMFS unit investigated the effects a shortened course of perioperative antimicrobial cover had on infective post-operative complications in patients who had surgical management of mid 1/3rd facial fractures. Method: As per the World Health Organisation (WHO) global action plan on antimicrobial resistance, with our microbiology team we developed and implemented a shortened antimicrobial protocol for use in the surgical management of mid 1/3rd facial fractures. Following protocol implementation, the records of 55 patients who underwent surgery for their mid 1/3 facial fractures between May 2019 and May 2020 were reviewed. Results: Of 55 patients who underwent surgical management of mid 1/3rd facial fractures 28/55 (50.9%) were prescribed a shortened course of perioperative antimicrobials depending on whether an intra or extra oral surgical approach was used, whilst 27/55 (49.1%) were prescribed a longer course of antimicrobials. Of those given a shortened course of antimicrobials 1/28 (3.6%) experienced infective post-operative complications. Conversely 4/27 (14.8%) of those given a longer course of antibiotics experienced infective post-operative complications. Conclusions: This data supports growing evidence that shorter courses of antimicrobials are appropriate in the surgical management of facial fractures. As OMFS surgeons we can utilise evidence-based medicine to provide optimal surgical care whilst simultaneously contributing to healthcare professionals' obligations to tackle the increasing challenge of antimicrobial resistance.